The Effectiveness of Differentiated Content through QuizWhizzer on Listening Comprehension and Motivation - Fadillah, Fika Nurul; Sunubi, Abdul Haris; Arqam, Arqam; Tjalla , Magdahalena; Dalle, Ambo (IAIN KENDARI, 2026)
This study aimed to investigate the effectiveness of implementing Differentiated Instruction through QuizWhizzer in improving students’ listening comprehension and learning motivation. It employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles. The participants of this study were 21 sixth-grade students. The data were collected through tests and observations. The tests were used to measure the improvement of students’ listening comprehension, meanwhile observations were conducted to assess students’ learning motivation during the teaching and learning process. Differentiated Instruction was implemented by grouping students based on their learning profiles, especially their learning styles and providing the materials (differentiated content) through QuizWhizzer according to students’ learning style. The results revealed that the implementation of Differentiated Instruction through QuizWhizzer was effective in improving students’ listening comprehension. This was evidenced by the increase in the students’ mean scores from 40 in pre-action to 70.52 at the end of Cycle I, and further increased to 79.95 at the end of Cycle II. In addition, students’ learning motivation also improved, as indicated by the observation results, which increased from an average score of 82.15 at the beginning of the implementation to 95.64 at the end of Cycle II, categorized as very good. Based on the findings, it can be concluded that the implementation of Differentiated Instruction through QuizWhizzer was effective in improving the listening comprehension and learning motivation of the sixth-grade students.